Distributed collaboration in design education: practising designer and client roles. (30th March 2009) - Lauche, Kristina; Bohemia, Erik; Connor, Chris; Badke-Schaub, Petra
Changes in industry require new forms of design education that better prepare students for the realities of concurrent engineering, increased involvement of suppliers in agile manufacturing, and the digitisation and virtualisation of collaboration. This article outlines these challenges for virtual design collaboration and reports first experiences of a distributed design studio (DDS) established between three European universities. In the DDS, students were taught core skills for virtual collaboration and could practice designer-client interaction in an experiential learning environment. The results of a course evaluation (during, at the end and one year after) show that students positively evaluated their own skill development. Student and staff feedback indicated that the embodiment phase proved to be more challenging and the evidence showed it coincided with reduced communication. Overall, the studio format can be seen as a suitable and realistic environment for practicing the relevant skills for virtual teamwork and designer-client communication. As a teaching initiative across institutions, it also served as personal development for staff.